Relationships between keratometry and collagen fibrillar structure of cornea by circular polarization biomicroscopy - Hwang, Hosik; Kim, Eun Chul; Kim, Man Soo (Cornea, 2011)
To evaluate the relationships between keratometry and collagen fibrillar structure of cornea by circular polarization biomicroscopy. Thirty-four subjects (63 eyes) were included in this study. Intraocular pressure (IOP) was measured, and keratometry was done with an automated keratometer. When the corneal astigmatism was larger than 0.75 diopter, corneal topography was done. After pupil dilation, the examiner placed a circular polarizing filter in front of the subject's eye. The images were captured by a camera connected to the slit lamp. Interfocal distance and angle were measured with ImageJ. The correlations between corneal astigmatism and interfocal distance-angle were examined by double angle vector diagram. Scalar analyses were done for the correlations between subject age and interfocal distance, between IOP and interfocal distance, and between mean cornea power and interfocal distance. The mean age of the 34 subjects was 59 ± 16 years. Mean interfocal distances and angles determined by double angle vector diagram were 4.67 mm and -20.5 degrees in the right eye and 3.73 mm and +24.2 degrees in the left eye. The correlation between age and interfocal distance and between IOP and interfocal distance were statistically insignificant (P = 0.913 and 0.361, respectively). The interfocal distance and angle showed no statistically significant correlation with corneal astigmatism by vector analysis (P = 0.221 and 0.850, respectively). The fibrillar structure pattern in circular polarizing biomicroscopy showed no statistically significant relationship with the bow tie pattern in corneal topography (P = 0.762). However, analysis of the correlation between mean corneal power and interfocal distance showed a statistically significant, but weak positive correlation (r = 0.326, P = 0.019). Interfocal distance determined through circular polarizing biomicroscopy showed a positive correlation with mean corneal power. But age, IOP, and corneal astigmatism did not show a significant correlation with interfocal distance and angle.